Educational Needs Assessment of ED Nurses Regarding the Care for Major Trauma Patients at Prince Mohammed Bin Nasser Hospital - Hamdi, Waleed Mohammed (Journal of medical and pharmaceutical sciences, 2019)
This study aimed to conduct an educational need assessment (ENA) to assess ED nurses’ skills in managing trauma patients in Saudi Arabia at the Prince Mohammed Bin Nasser (PMBN) Hospital in Jazan city. Methods: to achieve the study objectives, the descriptive analytical approach was applied where a paper-based survey was used for data collection. Results: 62.5% of the ED nurses who responded were unsure regarding their confidence in managing patients with pelvis and femur fractures. Similarly, 50% of the ED nurses who responded were undecided regarding their confidence in caring for chest tubes. 43.75% of participants were unsure about their confidence in fluid resuscitation and hypothermia management. In addition, 31% were unsure regarding their confidence in large bore cannula insertion and 6.25% were not confident. 68.7% of participants reported having difficulties identifying and locating obstetrics instruments and 62.5% of participants were hesitant regarding their confidence in caring for obstetric trauma and providing specific procedures for assessing infants’ heart rate. Conclusion: This study has shown the significance of applying the ENA to determining and prioritizing educational needs of ED nurses and it has found that ED nurses at the PMBN have difficulties in five major areas when dealing with trauma patients.
Keywords: trauma care; emergency department nurses; injury; trauma education